The acinar differentiation determinant PTF1A inhibits initiation of pancreatic ductal adenocarcinoma - Krah, Nathan M; De La O, Jean-Paul; Swift, Galvin H; Hoang, Chinh Q; Willet, Spencer G; Chen Pan, Fong; Cash, Gabriela M; Bronner, Mary P; Wright, Christopher VE; MacDonald, Raymond J; Murtaugh, L Charles (eLife, 2015)
Understanding the initiation and progression of pancreatic ductal adenocarcinoma (PDAC) may provide therapeutic strategies for this deadly disease. Recently, we and others made the surprising finding that PDAC and its preinvasive precursors, pancreatic intraepithelial neoplasia (PanIN), arise via reprogramming of mature acinar cells. We therefore hypothesized that the master regulator of acinar differentiation, PTF1A, could play a central role in suppressing PDAC initiation. In this study, we demonstrate that PTF1A expression is lost in both mouse and human PanINs, and that this downregulation is functionally imperative in mice for acinar reprogramming by oncogenic KRAS. Loss of Ptf1a alone is sufficient to induce acinar-to-ductal metaplasia, potentiate inflammation, and induce a KRAS-permissive, PDAC-like gene expression profile. As a result, Ptf1a-deficient acinar cells are dramatically sensitized to KRAS transformation, and reduced Ptf1a greatly accelerates development of invasive PDAC. Together, these data indicate that cell differentiation regulators constitute a new tumor suppressive mechanism in the pancreas.
Keywords: pancreatic cancer; differentiation; pancreatitis